2020
DOI: 10.1016/j.ebiom.2020.102989
|View full text |Cite
|
Sign up to set email alerts
|

Cell motility and migration as determinants of stem cell efficacy

Abstract: Background Stem cells` (SC) functional heterogeneity and its poorly understood aetiology impedes clinical development of cell-based therapies in regenerative medicine and oncology. Recent studies suggest a strong correlation between the SC migration potential and their therapeutic efficacy in humans. Designating SC migration as a denominator of functional SC heterogeneity, we sought to identify highly migrating subpopulations within different SC classes and evaluate their therapeutic properties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…However, definitively demonstrating which type of intranasally delivered stem cells perform best in reaching appropriate targets and have the best restorative or therapeutic effect may be difficult. We agree with the conclusion of Danielyan et al that the motility and migratory potential of stem cells can serve as predictors of their therapeutic efficacy because they all relate to the functional heterogeneity of stem cells [ 40 ].…”
Section: Types Of Stem Cells Administered By Transnasal Routesupporting
confidence: 92%
“…However, definitively demonstrating which type of intranasally delivered stem cells perform best in reaching appropriate targets and have the best restorative or therapeutic effect may be difficult. We agree with the conclusion of Danielyan et al that the motility and migratory potential of stem cells can serve as predictors of their therapeutic efficacy because they all relate to the functional heterogeneity of stem cells [ 40 ].…”
Section: Types Of Stem Cells Administered By Transnasal Routesupporting
confidence: 92%
“…However, whether a general enhancement of astroglial motility will lead to more effective targeting of Aβ plaques in vivo remains a matter for future investigations. Previous studies have demonstrated the improvement of Aβ plaques and soluble fragments’ clearance from the brains of 3xTg-AD and APP/PS1 mice treated with mesenchymal stem cells (MSC) by simply enhancing the migratory properties of MSC via the selection of highly migratory subpopulations for cell transplantation [ 47 ]. ARBs as potential enhancers of cell migration may be tested for their influence on the migratory properties of different cell therapeutics (adult stem cells, induced pluripotent stem cells, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Surface proteins such as CD271, CD146, MSCA-1, CD106, CD119, CD140a, or distinct mRNA signatures, defining cell clusters within MSC preparations, could be assigned to MSC functions such as differentiation, tissue regeneration, immunomodulation, or wound healing ( Jones and Schäfer, 2015 ; Wu et al, 2016 ; Khong et al, 2019 ; Kuci et al, 2019 ). Moreover, MSC subpopulations’ motility and adhesion capacities can affect their therapeutic efficacy ( Danielyan et al, 2020 ; Schäfer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these observations have not been elucidated completely, but the considerable heterogeneity of MSC preparations may be a relevant contributor. The composition of MSC preparations varies between donors ( Siegel et al, 2013 ), and there is emerging evidence linking MSC subpopulation phenotypes to their therapeutic potential ( Rennert et al, 2016 ; Khong et al, 2019 ; Kuci et al, 2019 ; Danielyan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%